Characterization of the genomic breakpoint and chimeric transcripts in the EWS-WT1 gene fusion of desmoplastic small round cell tumor. - Gerald, W L (1995)
Desmoplastic small round cell tumor is a recently recognized distinctive tumor shown to be associated with a recurrent translocation, t(11;22)(p13;q12), and rearrangement of the genes for Ewing sarcoma (EWS) and Wilms tumor (WT1). A genomic DNA fragment containing the EWS-WT1 gene fusion has been isolated from a desmoplastic small round cell tumor, and the breakpoint has been characterized. The breakpoints involve the intron between EWS exons 7 and 8 and the intron between WT1 exons 7 and 8. Chimeric transcripts corresponding to the fusion gene were detected in four of six cases studied. Analysis of these transcripts show an in-frame fusion of RNA encoding the amino-terminal domain of EWS to both alternatively spliced forms of the last three zinc fingers of the DNA-binding domain of WT1. Desmoplastic small round cell tumor represents the third tumor type associated with translocation of EWS and the first tumor associated with consistent translocation of WT1. The chimeric products are predicted to modulate transcription at WT1 target sites and contribute to development of this unique tumor.